Silicon application induces changes C:N:P stoichiometry and enhances stoichiometric homeostasis of sorghum and sunflower plants under salt stress - Calero Hurtado, Alexander [UNESP]; Chiconato, Denise Aparecida [UNESP]; Prado, Renato de Mello [UNESP]; Sousa Junior, Gilmar da Silveira [UNESP]; Olivera Viciedo, Dilier [UNESP]; Piccolo, Marisa de Cássia (Elsevier, 2020)
Beneficial effects of silicon (Si) on growth have been observed in some plant species, reportedly due to stoichiometric changes of C, N, and P. However, little is known about the effects on the stoichiometric relationships between C, N, and P when silicon is supplied via different modes in sorghum and sunflower plants under salt stress conditions. Therefore, the current study was performed to investigate the impact of differing modes of Si supply on shoot biomass production and C:N:P stoichiometry in sorghum and sunflower plants under salt stress. Two experiments were performed in a glass greenhouse using the strong Si-accumulator plant sorghum, as well as the intermediate type Si-accumulator sunflower, both of which were grown in pots filled with washed sand. Plant species were cultivated for 30 days in the absence or presence of salt stress (0 or 100 mM) and supplemented with one of four Si treatments: control plants (without Si), 28.6 mmol Si L−1 via foliar application, 2.0 mmol Si L−1 via nutrient solution, and combined application of foliar and nutrient solution, each group with five replications. The results revealed that supplied Si modified the C, N, and P concentrations, thereby enhancing the C:N:P stoichiometry and shoot dry matter of sorghum and sunflower plants under salt stress. Both application of Si via nutrient solution, as well as combined application via foliar and nutrient solution, increased the C:N ratio in both plant species under salt stress, but in sorghum plants decreased the C:P and N:P ratios and increased the shoot biomass production by 39%, while in sunflower plants increased the C:P and N:P ratios and increased the shoot biomass production by 24%. Our findings suggest that salt stress alleviation by Si impacts C:N:P stoichiometric relationships in a variable manner depending on the ability of the species to accumulate Si, as well as the route of Si administration.
Keywords: Carbon; Ecological stoichiometry; Helianthus annuus; Macronutrients; Salinity; Sorghum bicolor